How disruptive start-ups change the world of warehouse logistics - Julia Feldt; Henning Kontny; Frank Niemietz (Data Science and Innovation in Supply Chain Management: How Data Transforms the Value Chain. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 29, 2020)
Purpose: New technical solutions in logistics change the ways of working within warehouses on different levels, from warehouse layouts and concepts of goods picking to process planning and human resources. Thus, disrupting the previous practice in its core. Methodology: In order to evaluate the impact of the new technologies on the ware-house operations, the multiple case study approach was used. To gain a deeper un-derstanding of the changes within logistics processes, the results of the deep-dive analysis are summarized using morphologic box methodology. Findings: Presented solutions such as AutoStore, Kiva and CarryPick can lead to a substantial increase in the speed of order picking while staying very flexible and demanding significantly less of expensive warehouse space. Still, the implementation of these technologies requires a systematic approach with clearly stated goals. Originality: In contrary to available papers which are concentrating on a single case study with application of one technology at one particular company, the presented paper analyses several solutions comparing them with each other. Additionally, the research evaluates the impact of the technologies on logistic processes and warehouse layouts. Thus, creating value for practitioners looking for solutions to optimize intralogistics.
urn:nbn:de:gbv:830-882.0114870; hdl:10419/228914; https://econpapers.repec.org/RePEc:zbw:hiclpr:29
Keywords: 650; Logistics; Industry 4.0; Digitalization; Innovation; Supply Chain Management; Artificial Intelligence; Data Science